2013
DOI: 10.1186/1746-1596-8-169
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in plasminogen activator inhibitor-1 predict susceptibility to steroid-induced osteonecrosis of the femoral head in Chinese population

Abstract: BackgroundSteroid usage has been considered as a leading cause of non-traumatic osteonecrosis of the femoral head (ONFH), which is involved in hypo-fibrinolysis and blood supply interruption. Genetic polymorphisms in plasminogen activator inhibitor-1 (PAI-1) have been demonstrated to be associated with ONFH risk in several populations. However, this relationship has not been established in Chinese population. The aim of this study was to investigate the association of PAI-1 gene polymorphisms with steroid-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Environmental factors include type of prosthesis, implant design, material, surgical technique, fixation method, and postoperative rehabilitation procedure have been widely studied [ 13 , 14 ], but more and more attention is paid to the genetic factors like single nucleotide polymorphisms (SNPs). SNPs are genetic variations that are considered biologically normal and can be found in at least 1% of the population, which may contribute towards individual susceptibilities to certain pathological conditions [ 15 , 16 ]. Various gene SNPs of GNAS1, TNF-238, TNF-a, IL6-174, MMP1, MMP2, and et al were reported to be associated with increased prosthetic loosening.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors include type of prosthesis, implant design, material, surgical technique, fixation method, and postoperative rehabilitation procedure have been widely studied [ 13 , 14 ], but more and more attention is paid to the genetic factors like single nucleotide polymorphisms (SNPs). SNPs are genetic variations that are considered biologically normal and can be found in at least 1% of the population, which may contribute towards individual susceptibilities to certain pathological conditions [ 15 , 16 ]. Various gene SNPs of GNAS1, TNF-238, TNF-a, IL6-174, MMP1, MMP2, and et al were reported to be associated with increased prosthetic loosening.…”
Section: Introductionmentioning
confidence: 99%
“…PAI-1 is the main and fast-acting inhibitor of fi brinolysis, it inhibits tissue plasminogen activator (tPA) and urokinase (uPA), the activators of plasminogen. Therefore, it inhibits fi brinolysis and promotes thrombosis (56,(72)(73)(74). Increased plasma levels of the PAI-1 are associated with an increased incidence of trombophilia and AVN.…”
Section: Genetic Polymorphisms Involved In the Vascular Systemmentioning
confidence: 99%
“…Increased plasma levels of the PAI-1 are associated with an increased incidence of trombophilia and AVN. High levels of PAI-1, caused by PAI-1 gene polymorphism, either as a consequence of treatment with GCs, may lead to disturbance in blood fl ow to the femoral head and could result in bone AVN (56,73). French et al with other experts from Children's Oncology Group in 2008 pointed out the potential of PAI-1 polymorphism, that could predict AVN of bones.…”
Section: Genetic Polymorphisms Involved In the Vascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…There were much less alcoholic female ONFH patients (5.9%) (Cui et al, ). Similarly, genetic factors play an important role in the development of steroid‐induced femoral head necrosis (Li et al, ; Wang et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%